Characterizing the Critical Zone Using Borehole and Surface Nuclear Magnetic Resonance - Flinchum, B.A. (2020)
Understanding critical zone (CZ) structure below the first few meters of Earth's surface is challenging and yet important to understand hydrologic and surface processes that influence life on Earth. Nuclear magnetic resonance (NMR) is an emerging geophysical tool that can quantify the volume of groundwater and pore‐scale properties. Nuclear magnetic resonance has potential to aid in CZ studies, but it can be difficult to collect high‐quality NMR data in weathered and fractured rock. We present data from seven surface NMR soundings and six borehole NMR profiles collected on a weathered and fractured granite in the Laramie Range, Wyoming. First, we show that it is possible to collect high‐quality surface NMR data in a fractured rock. Second, we use the NMR data to delineate the weathering profile into three distinct zones—unsaturated saprolite, saturated saprolite, and fractured rock—and show that the surface NMR signal is dominated by saturated saprolite. Third, we show that lateral heterogeneity significantly reduces the surface NMR signal magnitude, which suggests that the boundary dividing saprolite and fractured rock is laterally heterogeneous. The NMR measurements, when combined with previously collected seismic refraction data, provide a unique opportunity to define the lateral heterogeneity of the boundary dividing saprolite and weathered bedrock in an eroding landscape underlain by crystalline rock.